(untitled) (Journal of the College of Basic Education, 2022)
Research SummaryThe research consists of an introduction, three sections, and a conclusion, followed by a list of sources.The poem chosen for the research topic is the one whose beginning is:upon determined people determination will beThe three research topics are:The first topic: a linguistic reading of the poem, and this reading is related to linguistically analyzing the poem.The second topic: the compositional analysis of the poem, which is related to the composition of sentences, and includes nouns, verbs, and clues in this composition.The third topic: the semantic phenomena in the poem, and this topic took most of the research because it came in two parts:The first section: relates to vocabulary in general, and what it contains of semantic fields, levels of semantics, and areas of semantic expression.The second section: related to formulas for derivatives and plurals, then the conclusion, in which I dealt with the most important results that I reached.